Sensitivity of Fusarium culmorum to triazoles: impact of trichothecene chemotypes, oxidative stress response and genetic diversity. Issue 6 (9th December 2016) - Hellin, Pierre; Scauflaire, Jonathan; Van Hese, Viviane; Munaut, Françoise; Legrève, Anne
Abstract: BACKGROUND: Fusarium culmorum is a fungal pathogen occurring worldwide on various weeds and important crops. Triazoles have been shown to be the most effective fungicide for managing Fusarium spp., but little is known about their specific activity on F. culmorum . RESULTS: The sensitivity of 107 F. culmorum strains to triazoles was assessed using microtitre plate assays. The EC50 values ranged from 0.14 to 1.53 mg L −1 for tebuconazole and from 0.25 to 2.47 mg L −1 for epoxiconazole. Cross‐resistance to both azoles was found ( r = 0.61). F. culmorum appeared to be significantly more sensitive than F. graminearum or F. cerealis . No increase in the mean EC50 was observed over time, which might be related to an unfavourable fitness cost, measured here as fungal growth. On average, nivalenol‐producing strains of F. culmorum were significantly more resistant than deoxynivalenol‐producing strains. The relationship between resistance and chemotype‐dependent adaptation to oxidative stress was investigated, but remained unclear. No link between inter‐simple sequence repeat (ISSR) genetic diversity and triazole resistance could be established. CONCLUSION: Fungicide use might not be a driving force in the evolution of F. culmorum, and the benefit of a resistance trait probably does not outweigh its costs. © 2016 Society of Chemical Industry